SIGNIFICANCE OF DIGITAL COMPETENCE OF THE SPECIALIST OF AUTO TRANSPORT PROFILE IN PROFESSIONAL ACTIVITIES - Kovalchuk, Vasyl; Soroka, Valerii; Zaika, Artem (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Every day modern technology is radically changing various industries at ever faster paces. The modern era of innovation is accompanied by a number of inventions and know-how – from robotization of production to the introduction of artificial intelligence at state levels.An important component of the training of future specialists in vocational education is the formation of digital competency which involves the ability and ability of the logical and systemic use of digital technologies.The automotive industry is currently undergoing structural changes due to the rapid development and implementation of modern digital technologies such as programmed electric vehicles, unmanned vehicles, robotic mechanisms for controlling mechanisms, remote control and contactless operations.The purpose of the study is a theoretical justification and experimental study of the levels of digital competence formation of future specialists in the automotive industry.To achieve the goal of the study, the following methods were used: analysis, synthesis, comparison, generalization, questioning.The article analyzes the features of the formation and development of digital competence of a motor transport specialist in the process of their preparation in vocational education institutions of developed countries.In the study the total number of respondents was 72 participants. The study was conducted on the basis of the results obtained in the process of questioning graduate students of the specialty "Transport" at the Professional and Pedagogical College of the Glukhov National Pedagogical University named after Alexander Dovzhenko. Based on the results of the questionnaire, the level of digital competency of future specialists in the automotive industry was established.The obtained results allow us to identify some problems in the formation and development of digital competence in the preparation of a motor transport specialist in vocational education institutions.